Thematic and Design Paradigms in Minnesota’s Official Highway Maps, 1936-2018 - Churchhill, Haley; Myers, Josie; Zeitler, Ezra (My University, 2019)
Since the mid-1930s, highway maps distributed by the State of Minnesota have become more detailed and comprehensive while integrating themes reflecting aspects of the state’s diverse economic activities. This study identifies the themes emphasized in Minnesota highway maps, how they have changed, and how technological advancements have influenced the cartographic elements employed in their design. A manifest content analysis of imagery and text included in eleven highway maps produced by the State of Minnesota between the years of 1936 and 2017 reveals several thematic paradigms focused on: “Up North” tourism during the 1930s, patriotism and history in the 1940s and 1950s, wilderness-related tourism during the 1960s and into 1970s, when new interstate and highway systems were emphasized, and a shift in emphasis towards the state’s urban cultural amenities from the late 1980s to the present. Recent scholarship in feminist cartography informed a critical latent analysis of the sampled maps highlighted an equitable inclusion of women but revealed problematic representations of Indigenous peoples. Considering the current print/digital navigation crossroads in society, we suggest that paper highway maps still meet the needs of their users and have the potential to be more inclusive in their design and thematic content.
Color poster with text, images, photographs, and maps.
Keywords: Highway maps; Minnesota; Map design; Posters